The Use of Biosilica to Increase the Compressive Strength of Cement Mortar: The Effect of the Mixing Method - Muradyan, Nelli G.; Arzumanyan, Avetik A.; Kalantaryan, Marine A.; Vardanyan, Yeghiazar V.; Yeranosyan, Mkrtich; Ulewicz, Malgorzata; Laroze, David; Barseghyan, Manuk G. (Materials, 2023)
In this work, the effect of biosilica concentration and two different mixing methods with Portland cement on the compressive strength of cement-based mortars were investigated. The following values of the biosilica concentration of cement weight were investigated։ 2.5, 5, 7.5, and 10 wt.%. The mortar was prepared using the following two biosilica mixing methods: First, biosilica was mixed with cement and appropriate samples were prepared. For the other mixing method, samples were prepared by dissolving biosilica in water using a magnetic stirrer. Compressive tests were carried out on an automatic compression machine with a loading rate of 2.4 kN/s at the age of 7 and 28 days. It is shown that, for all cases, the compressive strength has the maximum value of 10% biosilica concentration. In particular, in the case of the first mixing method, the compressive strength of the specimen over 7 days of curing increased by 30.5%, and by 36.5% for a curing period of 28 days. In the case of the second mixing method, the compressive strength of the specimen over 7 days of curing increased by 23.4%, and by 47.3% for a curing period of 28 days. Additionally, using the first and second mixing methods, the water absorption parameters were reduced by 22% and 34%, respectively. Finally, it is worth noting that the obtained results were intend to provide valuable insights into optimizing biosilica incorporation in cement mortar. With the aim of contributing to the advancement of construction materials, this research delves into the intriguing application of biosilica in cement mortar, emphasizing the significant impact of mixing techniques on the resultant compressive strength.